Evolution of Human Resource Management – A Review Article (Journal of Pharmaceutical Negative Results, 2022)
Success at the highest levels of a business and developing a sustainable competitive advantage depend on its human resources. The study's primary goal is to trace HRM's historical development. To that end, researchers shed light on HRM's many developmental stages and antecedents. The study's authors define HRM and its variety by delving into how various HRM techniques are used in firms and how they affect business outcomes. After thoroughly examining the idea of human resource management, the research team believes that successful businesses employ HRM in a way that maximizes their potential. Human Resource Management is an integrated management approach that originated from the study of organizational psychology. Over time, this method's function has evolved into a strategic one. Departments dedicated to human resource management have become more critical to the success of enterprises in the modern era of organizational achievement, human resource management, strategic human resource management, and human capital.